2019
DOI: 10.1111/jpn.13150
|View full text |Cite
|
Sign up to set email alerts
|

Association of A‐FABP gene polymorphism and mRNA expression with intramuscular fat content (IMF) in Baicheng‐You chicken

Abstract: This study aims to assess the association of polymorphisms and mRNA expression of adipocyte‐type fatty acid‐binding protein (A‐FABP) with intramuscular fat (IMF) in the breast muscle (BM) and leg muscle (LM) of Baicheng‐You chickens (BYCs). A total of 180 chickens, including sixty black Baicheng‐You chickens (BBYCs), sixty silky Baicheng‐You chickens (SBYCs) and sixty white Baicheng‐You chickens (WBYCs), were reared from 1 to 120 day. A polymerase chain reaction–single‐strand conformation polymorphism strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…The upregulation of all these genes indicated a higher lipid biosynthesis in the HTG group. Previous studies have identified numerous candidate genes ( PPARs , FABPs , LPL , SCD , KLFs and ACSLs ) related to IMF deposition in chickens [710]. Most of these genes are associated with TG deposition in this study, indicating they might play an important role in IMF deposition by regulating TG metabolism.…”
Section: Discussionsupporting
confidence: 50%
“…The upregulation of all these genes indicated a higher lipid biosynthesis in the HTG group. Previous studies have identified numerous candidate genes ( PPARs , FABPs , LPL , SCD , KLFs and ACSLs ) related to IMF deposition in chickens [710]. Most of these genes are associated with TG deposition in this study, indicating they might play an important role in IMF deposition by regulating TG metabolism.…”
Section: Discussionsupporting
confidence: 50%
“…Three genotypes of the A-FABP gene first exon, AA, AB, and BB were examined by PCR-SSCP. The intramuscular fat content with the AA genotype was significantly higher than that with the AB genotype in the Baicheng-You Chickens [50], three-Yellow Chickens and Hetian-Black Chickens [51].…”
Section: Deposition In Chickens Plant Extracts Regulate the Expressio...mentioning
confidence: 81%
“…Three genotypes of the A-FABP gene first exon, AA, AB, and BB were examined by polymerase chain reaction-single-strand conformation polymorphism. The intramuscular fat content with the AA genotype was significantly higher than that with the AB genotype in the Baicheng-You Chickens [ 50 ], three-Yellow Chickens and Hetian-Black Chickens [ 51 ]. iii) According to the research of Fu et al [ 52 ], five transcriptional regulatory factors including CCAAT/enhancer binding protein α and β (CEBPα, β), PPARα, PPARγ, sterol-regulatory element binding proteins (SREBP-1) influenced the fat deposition of Beijing-You chickens.…”
Section: Plant Extracts Regulate the Lipid Metabolism And Fat Deposit...mentioning
confidence: 99%